Post-treatment method for additive manufacturing metal part
Through micro-scale laser impact enhancement and sandblasting treatment, the surface roughness and residual stress problems of metal additive manufacturing components are solved, fatigue performance is improved, post-treatment process is simplified, and post-treatment process is suitable for large components and on-site emergency support.
Patent Information
- Application Number
- CN202411315453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The surface roughness and internal residual tensile stress formed by metal additive manufacturing components under the action of high energy beams lead to poor fatigue performance. The existing post-treatment methods are complex, time-consuming and unsuitable for large parts and on-site rapid spare parts manufacturing.
Micro-scale laser impact enhancement technology is used to perform high-frequency scanning treatment on weak fatigue parts. The micro-scale small energy laser directly acts on the surface of the component to melt the burr, reduce the roughness, and the residual compressive stress is formed through laser-induced shock waves, combined with sandblasting Treatment improves surface finish and eliminates heat treatment and machining.
It significantly improves the fatigue performance of additive manufacturing components, simplifies the post-processing process, improves efficiency and applicability, and is suitable for large components and on-site emergency support.
Smart Images

Figure CN119187609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of additive manufacturing of metal materials, and in particular to a post-processing method for additively manufactured metal parts. Background Art
[0002] Additive Manufacturing (AM) is a new manufacturing technology that uses sintering, melting, light curing, and spraying to stack actual components layer by layer from the bottom up, based on a computer-designed digital model. Compared with the traditional subtractive manufacturing method of blank + machining, it has the advantages of strong design, one-time forming of complex structures, and integrated integration of multiple components. Especially in the field of additive manufacturing of metal / alloy materials, companies such as Boeing, GE, Pratt & Whitney in the United States, Rolls-Royce in the United Kingdom, and MTU in Germany have applied this technology to the manufacture of complex components for major equipment such as aircraft and aero engines, which can greatly reduce the difficulty and economic cost of manufacturing complex components and significantly improve the efficiency of component manufacturing.
[0003] The additive manufacturing process of metal materials is essentially a material forming process in which metal raw materials are rapidly melted and solidified under the action of high-energy beams. It is a non-equilibrium state under extreme conditions, with large surface roughness and residual tensile stress inside, which leads to poor fatigue performance of additively manufactured parts, making it difficult to meet the mechanical performance requirements of equipment, restricting engineering applications. At present, in engineering practice, in order to eliminate the influence of adverse factors such as organization, stress and surface roughness, the additively manufactured parts will be first heat treated to regulate the organization and stress, and then the surface roughness will be reduced by machining such as milling to ensure the fatigue performance of the additively manufactured parts. However, the above post-processing is not only complicated, time-consuming, costly, and has a general anti-fatigue effect, but also no longer applicable to large parts and on-site rapid spare parts manufacturing. It is urgent to develop a simple, convenient and efficient post-processing method for additively manufactured parts, which can ensure the fatigue performance of parts on the basis of eliminating complex processing processes such as hot isostatic pressing, heat treatment, and machining after additive manufacturing.
[0004] Laser shock peening (LSP) is a surface fatigue resistance manufacturing technology that uses short pulse (nanosecond level), high power (GW level) strong laser to interact with the absorption protective layer, and forms a high pressure (GPa level) plasma shock wave under the action of the constraint layer. The mechanical effect of the high pressure shock wave causes plastic deformation of the surface of the metal parts, generating gradient residual compressive stress, thereby significantly improving its fatigue performance. Microscale laser shock peening is a special form of laser shock peening method. The spot size of the pulsed laser used is in the micrometer level, and the laser energy is in the millijoule level. The laser ablation effect is weak and there is no obvious remelting crack. There is no need to use an absorption protective layer. The constraint layer can be formed by water flow or underwater, etc. The surface roughness and internal residual stress of the material can be regulated, and its fatigue performance can be improved while improving the surface quality. It can be used as a post-processing method for additive manufacturing parts, especially for the emergency support of additive manufacturing site. It has important value and significance. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a post-processing method for additively manufactured parts, and the specific technical solution is as follows:
[0006] A post-processing method for additively manufactured metal parts comprises the following steps:
[0007] S1. Perform additive manufacturing on a metal part to obtain an additively manufactured part, and use an ultrasonic cleaning machine and / or a hair dryer to deeply clean the surface of the additively manufactured part to remove metal powder remaining on the surface;
[0008] S2. Use finite element simulation method to analyze the fatigue working stress distribution of additively manufactured metal parts under actual service load conditions and determine the fatigue weak points;
[0009] S3. Use micro-scale laser shock strengthening method to perform high-frequency scanning treatment on fatigue weak parts of additively manufactured metal parts. The thermal effect of direct action of micro-scale low-energy laser on the surface of the parts melts the burrs, smoothes them and reduces the roughness. At the same time, the mechanical effect of laser-induced shock waves forms residual compressive stress on the surface.
[0010] S4. Use a sandblasting machine to sandblast the entire surface of the additively manufactured metal part to remove 1 to 10 μm of the molten / heat-affected layer to further improve the surface finish of the part.
[0011] Optionally, the laser energy of the microscale laser shock strengthening is 100-500 mJ, the spot diameter is 0.3-0.5 mm, the laser pulse width is 10 ns, and the power density is 15-25 GW / cm 2The number of impacts is 3 to 5 times, the spot overlap rate is more than 50%, and the repetition frequency is more than 100Hz.
[0012] Optionally, during the microscale laser shock peening process, there is no need to use an absorption protective layer, and the constraint layer is applied by water-light coaxially, that is, the pulsed laser is transmitted in deionized water, which can greatly improve the impact depth and processing efficiency of microscale laser shock peening.
[0013] Optionally, metal parts are additively manufactured using laser powder bed fusion or powder bed electron beam melting methods.
[0014] Optionally, during the sandblasting process, the pressure is 10-20 MPa, preferably 12-20 MPa.
[0015] In summary, the post-processing method of additively manufactured metal parts of the present invention has at least the following beneficial effects:
[0016] Through the high-frequency scanning treatment of micro-scale laser shock strengthening, the surface of the additively manufactured metal parts undergoes plastic deformation, forming residual compressive stress with uniform surface and gradient distribution, eliminating the need for heat treatment process; through the direct ablation effect of micro-scale low-energy laser and the surface of the additively manufactured parts, the surface burrs can be melted and the surface roughness can be reduced, eliminating the need for mechanical processing; while eliminating complex and time-consuming processes such as heat treatment and mechanical processing, the fatigue performance of the parts can be improved, which will greatly expand the application scope of additively manufactured metal parts. The entire post-processing method has the advantages of simple principle, easy operation, fast and efficient, multifunctional composite, good anti-fatigue effect, strong engineering applicability, etc., and can be applied to special application scenarios such as large parts and equipment on-site emergency support. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A flow chart of a post-processing method for additively manufactured metal parts of the present invention;
[0018] Figure 2 Simulate the original surface morphology of blades for LPBF additive manufacturing of titanium alloy;
[0019] Figure 3 The surface morphology of the simulated blade of the titanium alloy manufactured by LPBF additive manufacturing under the post-processing method of the present invention;
[0020] Figure 4 The surface roughness comparison of the simulated blade of titanium alloy manufactured by LPBF additive manufacturing under the post-processing method of the present invention is shown;
[0021] Figure 5 This is a comparison of the deep microhardness of the simulated blade of titanium alloy manufactured by LPBF additive manufacturing under the post-processing method of the present invention;
[0022] Figure 6Comparison of residual stress on the surface of simulated blades made of titanium alloy by LPBF additive manufacturing under the post-processing method of the present invention;
[0023] Figure 7 Comparison of residual stress depth of simulated blades of titanium alloy manufactured by LPBF additive manufacturing under the post-processing method of the present invention;
[0024] Figure 8 The fatigue performance comparison of titanium alloy simulated blades manufactured by LPBF using the post-processing method of the present invention is shown. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0026] It should be noted that the microscale laser in the present application is a micrometer-level laser with a spot size less than 1 mm, and the low-energy laser refers to a millijoule-level laser with an energy less than 1 J.
[0027] First, see the attached Figure 1 As shown, the technical solution of the present invention provides a post-processing method for additively manufactured metal parts, which is implemented in the following steps:
[0028] S1. Perform additive manufacturing on metal parts by laser powder bed melting or powder bed electron beam melting to obtain additively manufactured parts, and perform deep cleaning on the surface of the additively manufactured parts by using an ultrasonic cleaner and / or a hair dryer to remove residual metal powder on the surface;
[0029] S2. Use finite element simulation method to analyze the fatigue working stress distribution of additively manufactured metal parts under actual service load conditions and determine the fatigue weak points;
[0030] S3. Use micro-scale laser shock strengthening method to perform high-frequency scanning treatment on fatigue weak parts of additively manufactured metal parts. The laser energy is 100-500mJ, the spot diameter is 0.3-0.5mm, the laser pulse width is 10ns, and the power density is 15-25GW / cm 2 The impact times are 3 to 5 times, the spot overlap rate is more than 50%, the repetition frequency is more than 100Hz, and there is no need to use an absorption protection layer. The constraint layer adopts the water-light coaxial application method, that is, the pulsed laser is transmitted in deionized water, which can greatly improve the impact depth and processing efficiency of micro-scale laser shock strengthening;
[0031] S4. Use a sandblasting machine to sandblast the entire surface of the additively manufactured metal part at 10-20MPa to remove 1-10μm of the molten / heat-affected layer to further improve the surface finish of the part.
[0032] In the absence of an absorption protective layer and a water-light coaxial constraint layer, microscale laser shock strengthening is used to perform high-frequency scanning processing on the additively manufactured metal parts. The mechanical effect of the laser-induced shock wave causes plastic deformation of the surface of the additively manufactured metal parts, forming a uniform and gradient-distributed residual compressive stress on the surface, which plays a role in heat treatment. Through the direct ablation effect of microscale low-energy laser and the surface of the additively manufactured parts, the surface burrs can be melted and the surface roughness can be reduced, which plays a role in mechanical processing. While eliminating complex and time-consuming processes such as heat treatment and mechanical processing, the fatigue performance of the parts can be improved.
[0033] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0034] Example 1: Post-processing of TC4 titanium alloy blades manufactured by LPBF Figure 1 The specific implementation process is as follows:
[0035] (1) Use CATIA and other 3D drawing software to perform 3D modeling of the blade to obtain a 3D solid model of the blade. Use Magics, EPHatch and other software to slice, fill, set printing process parameters, etc., and output the final data file that can be executed by the additive manufacturing equipment. The main printing process parameters of the titanium alloy blade are as follows: layer thickness 0.03mm, main power 200W, scanning speed 1000mm / s.
[0036] (2) On the laser powder bed melting equipment, TC4 titanium alloy powder is loaded, and the model data file is executed to print out the titanium alloy blade, and the blade is removed by wire cutting.
[0037] (3) The additively manufactured TC4 titanium alloy blade is placed in an ultrasonic cleaning machine, anhydrous ethanol is added, the surface of the blade is deeply cleaned to remove residual powder and stains, and then dried with hot air from a hair dryer.
[0038] (4) Fatigue working stress analysis is performed based on the actual working load of the titanium alloy blade, and it is determined that the curved step line area at the root of the blade is the fatigue weak point of the blade, where the fatigue stress is the largest and the life is the shortest.
[0039] (5) According to the basic mechanical properties of TC4 titanium alloy, the specific process parameters for microscale laser shock strengthening of titanium alloy blades are designed as follows: laser energy of 76 mJ, spot diameter of 0.4 mm, laser pulse width of 10 ns, and laser power density of 6.05 GW / cm 2 The spot overlap rate is 50%, and the impact number is 1 time, so that the burrs on the blade surface are melted and become smoother, the surface roughness is significantly reduced, and gradient residual compressive stress is formed on the blade surface to improve the fatigue performance of the blade.
[0040] (6) The entire surface of the additively manufactured titanium alloy blade is subjected to high-pressure (pressure of 15 MPa) rapid sandblasting by using a sandblasting machine to remove the surface molten layer in the micro-laser shock peening treatment area to further improve the surface finish of the titanium alloy blade.
[0041] Example 2: Post-processing of LPBF additively manufactured GH3625 nickel-based high-temperature alloy turbine blades. Figure 1 The specific implementation process is as follows:
[0042] (1) Use CATIA and other 3D drawing software to perform 3D modeling of turbine blades, obtain a 3D solid model of turbine blades, slice, fill, set printing process parameters, etc. through Magics, EPHatch and other software, and output the final data file executable by additive manufacturing equipment. The main printing process parameters of nickel-based high-temperature alloy turbine blades are as follows: layer thickness 0.03mm, main power 200W, scanning speed 1000mm / s.
[0043] (2) Load GH3625 nickel-based high-temperature alloy powder into the laser powder bed melting equipment, execute the model data file, print out the nickel-based high-temperature alloy turbine blades, and remove the blades by wire cutting.
[0044] (3) The additively manufactured nickel-based high-temperature alloy turbine blades are placed in an ultrasonic cleaning machine, anhydrous ethanol is added, the surface of the turbine blades is deeply cleaned to remove residual powder and stains, and then the blades are dried with hot air from a hair dryer.
[0045] (4) According to the actual working load of the nickel-based high-temperature alloy turbine blade, fatigue working stress analysis is carried out to determine that the tenon R area at the root of the blade is the fatigue weak part of the blade (the site corresponding to the maximum value is extended to the surrounding area;
[0046] Judge according to the corresponding application scenario), where the fatigue stress is the largest and the life is the shortest.
[0047] (5) According to the basic mechanical properties of nickel-based high-temperature alloys, the specific process parameters for micro-scale laser shock strengthening of the R zone of the tenon of nickel-based high-temperature alloy turbine blades are designed as follows: laser energy of 100 mJ, spot diameter of 0.4 mm, laser pulse width of 10 ns, and laser power density of 7.96 GW / cm 2 The spot overlap rate is 50%, and the impact number is 1 time, so that the burrs on the surface of the turbine blade are melted and become smoother, the surface roughness is significantly reduced, and a gradient residual compressive stress is formed on the surface of the turbine blade tenon R area, thereby improving the fatigue performance of the turbine blade.
[0048] (6) The entire surface of the additively manufactured GH3625 nickel-based high-temperature alloy turbine blade is subjected to high-pressure (pressure of 15 MPa) rapid sandblasting using a sandblasting machine to remove the surface molten layer in the micro-laser shock intensive treatment area to further improve the surface finish of the turbine blade.
[0049] Test comparison and results:
[0050] The titanium alloy simulated blades of the same batch as Example 1 were used as the test group, and the titanium alloy simulated blades without post-treatment after LPBF additive manufacturing were used as the reference group. The surface morphology was observed (scanning electron microscope) and roughness test (laser confocal microscope), microhardness test (GB / T 4340.1-2009 "Metal Vickers Hardness Test", using Vickers microhardness tester), residual stress test (GB / T 7704-2017 "Non-destructive Testing X-ray Stress Determination Method", using LXRD type X-ray diffraction residual stress tester of Canadian PROTO Company, using the tilt method, the target material is Cu target, the diffraction angle 2θ is 139°-142°, and the diffraction wavelength is 1.542nm. When performing the stress test in depth, the PROTO company POLISHER 8818V-3 electrolytic polishing machine is used to peel the material layer by layer, and the polishing liquid composition is 10% HClO 4 +90% CH 3 OH) and axial fatigue test (GB / T 3075 "Metal Axial Fatigue Test Method", using MTS multifunctional axial fatigue testing machine) and other comparative analysis shows that:
[0051] 1. The surface morphology of the two blades mentioned above was observed. The results are as follows: Figure 2 and Figure 3 As shown. Figure 2 and Figure 3 It can be seen that the burrs and spheroidization defects on the surface of the titanium alloy simulated blade after post-treatment of the present invention are significantly improved; from the surface roughness test results, such as Figure 4As shown, the surface roughness Ra of the titanium alloy simulated blade after post-treatment of the present invention is reduced from 31.45 μm to 23.00 μm, and the surface roughness is significantly improved, indicating that the method of the present application significantly improves the surface quality of additively manufactured metal parts.
[0052] 2. Microhardness test of the above two blades. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the surface of the titanium alloy simulated blade after post-treatment of the present invention forms a hardened layer with a depth gradient distribution of 400μm, which greatly improves the hardness of the surface of the titanium alloy simulated blade, indicating that the method of the present application can significantly improve the surface hardness of additively manufactured metal parts.
[0053] 3. The residual stress test results of the above two simulated blades are as follows: Figure 6 and Figure 7 As shown. Figure 6 and Figure 7 It can be seen that the surface of the titanium alloy simulated blade post-treated by the present invention forms a residual compressive stress of -207.9MPa, while the surface of the untreated titanium alloy blade has a residual tensile stress of 19.65MPa. Residual compressive stress is formed within a depth of 500μm, indicating that the method of the present application significantly improves the residual stress state of the additively manufactured metal parts, thereby improving the fatigue strength of the additively manufactured metal parts. Figure 8 As shown, the fatigue strength is improved by 16.3%.
[0054] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A post-processing method for additively manufactured metal parts, characterized in that: The following steps are involved: S1. Perform additive manufacturing on a metal part to obtain an additively manufactured part, and use an ultrasonic cleaning machine and / or a hair dryer to deeply clean the surface of the additively manufactured part to remove metal powder remaining on the surface; S2. Use finite element simulation method to analyze the fatigue working stress distribution of additively manufactured metal parts under actual service load conditions and determine the fatigue weak points; S3. Use micro-scale laser shock strengthening method to perform high-frequency scanning treatment on fatigue weak parts of additively manufactured metal parts. The thermal effect of direct action of micro-scale low-energy laser on the surface of the parts melts the burrs, smoothes them and reduces the roughness. At the same time, the mechanical effect of laser-induced shock waves forms residual compressive stress on the surface. S4. Use a sandblasting machine to sandblast the entire surface of the additively manufactured metal part to remove 1 to 10 μm of the molten / heat-affected layer to further improve the surface finish of the part.
2. The post-processing method for additively manufactured metal parts according to claim 1, characterized in that: The laser energy of the microscale laser shock strengthening is 100-500 mJ, the spot diameter is 0.3-0.5 mm, the laser pulse width is 10 ns, and the power density is 15-25 GW / cm 2 The number of impacts is 3 to 5 times, the spot overlap rate is more than 50%, and the repetition frequency is more than 100Hz.
3. The post-processing method for additively manufactured metal parts according to claim 1, characterized in that: During the microscale laser shock peening process, no absorption protection layer is provided, and the constraint layer is applied in a water-light coaxial manner.
4. The post-processing method for additively manufactured metal parts according to claim 1, characterized in that: Additive manufacturing of metal parts using laser powder bed fusion or powder bed electron beam melting.
5. The post-processing method for additively manufactured metal parts according to claim 1, characterized in that: During the sandblasting process, the pressure is 10-20 MPa.
Citation Information
Cited By
Titanium-aluminum-based alloy destressing additive manufacturing method
CN120587490A
